Pengaruh Etos Kerja Guru Terhadap Kinerja Guru SMP Muhammadiyah 11 Kota Makassar - Damayanti, Pradillah; Nurlaelah, Nurlaelah; Syahrul, Muhammad; Syahid, Akhmad; Subaedah, Subaedah (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study investigates the influence of work ethic on teacher performance at SMP Muhammadiyah 11 Makassar City. Considered as an important component that supports professionalism and learning success is teacher work ethic. In this study, a quantitative approach was used together with a survey. The relationship between work ethic and teacher performance was studied using inferential statistical techniques after data were obtained from questionnaires distributed to a number of participating teachers. The results of the study showed that there was a positive and significant correlation between work values ​​and teacher performance. Teachers who have high work enthusiasm tend to get good results, especially in terms of planning, implementing, and evaluating learning. This finding suggests that improving teacher work ethic helps improve the quality of education. Therefore, fostering work ethic is an important part of the continuous development of teacher professionalism.